Education in Saudi Arabia (Reviews of National Policies for Education, 2020)
Saudi Arabia has embarked upon an unprecedented reform agenda known as Vision 2030, which aims to create a dynamic, diverse and sustainable economy. To meet the demands of a 21st century, knowledge-based labour market, Saudi Arabia must develop a highly-skilled population, which puts education at the centre of Vision 2030. Saudi Arabia has made tremendous progress in expanding access to education and has achieved universal enrolment rates at primary and lower secondary levels. Nevertheless, most young Saudi Arabians leave school without having mastered the basic competences needed for success in future academic and professional endeavours. There are also widening disparities between students in terms of their access to high quality education and their subsequent learning outcomes. This review, developed in co-operation with the Ministry of Education of Saudi Arabia, analyses the strengths and challenges of the country's education system and makes recommendations to help improve student learning. It will be of interest to policy makers in Saudi Arabia and international audiences who wish to learn about the country's ambitious reform efforts